2003
DOI: 10.1159/000068559
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler Imaging of Choroidal Circulation in Patients with Asymmetric Age-Related Macular Degeneration

Abstract: We aimed at evaluating the possible role of choroidal perfusion abnormalities in the development of choroidal neovascularisation (CNV) in patients with age-related macular degeneration (AMD). Twenty-six patients who had non-exudative AMD in the first eye and CNV secondary to AMD in the fellow eye were enrolled. Blood flow velocities, vessel pulsatilities and resistivities were measured from ophthalmic artery, nasal and temporal posterior ciliary arteries using colour Doppler imaging. Systolic and diastolic vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…[51][52][53] The results of one of those studies suggested that irregular blood flow in the short posterior ciliary arteries may play a role in the pathogenesis of exudative ARMD. 51 There have been reports on the effect of various forms of treatment of exudative ARMD to the retrobulbar circulation.…”
Section: -53mentioning
confidence: 99%
“…[51][52][53] The results of one of those studies suggested that irregular blood flow in the short posterior ciliary arteries may play a role in the pathogenesis of exudative ARMD. 51 There have been reports on the effect of various forms of treatment of exudative ARMD to the retrobulbar circulation.…”
Section: -53mentioning
confidence: 99%
“…Although it has been reported that patients with unilateral CNV have reduced posterior ciliary artery flow velocities in both eyes, 79 other investigators have found that posterior ciliary artery blood velocities are more affected in the exudative eye than in the contralateral eye. 80 Another approach to studying the choroidal vasculature in AMD is based on angiographic techniques, although the extraction of quantitative data from the choroids based on angiograms is still difficult. However, a number of studies have characterized abnormalities in the choroidal circulation based on angiograms in patients with AMD.…”
Section: Degenerationmentioning
confidence: 99%
“…It was further postulated that removal of waste materials and the supply of nutritional substances as well as oxygen exchange to the neural retina is impaired due to choroidal vascular alterations [34]. In several studies using different techniques it has been shown that reduced choroidal blood flow is associated with AMD [35][36][37][38]. This theory is supported by correlation of AMD with diseases involving arteriosclerotic changes such as the carotid artery disease [38].…”
Section: Choroidal Circulation Theorymentioning
confidence: 99%
“…In several studies using different techniques it has been shown that reduced choroidal blood flow is associated with AMD [35][36][37][38]. This theory is supported by correlation of AMD with diseases involving arteriosclerotic changes such as the carotid artery disease [38]. Interestingly, most epidemiological studies, except for the Rotterdam Study [39], did not find a direct association of cardiovascular disease and AMD [40][41][42], however many factors for cardiovascular disease are also risk factors for AMD.…”
Section: Choroidal Circulation Theorymentioning
confidence: 99%